2013
DOI: 10.1177/0886260513505150
|View full text |Cite
|
Sign up to set email alerts
|

Victimization Experiences and Adolescent Substance Use

Abstract: Evidence indicates an association between victimization and adolescent substance use, but the exact nature of this relationship remains unclear. Some research focuses solely on the consequences of experiencing indirect victimization (e.g., witnessing violence), others examine direct victimization (e.g., being personally victimized), and still others combine both forms of victimization without assessing the relative impact of each on substance use. Furthermore, many of these studies only assess these relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 66 publications
0
16
1
Order By: Relevance
“…In addition, Oswald et al (80) suggested that early trauma may lead to enhanced sensitivity to substances and that this mechanism may underlie increased vulnerability for drug abuse. In a recent study conducted among adolescents, victimization experiences were associated with increased contemporaneous substance use, while the impact on substance use declined over time (34). Lifetime tobacco and drug use predicted the GPS in the present study, and their effects also interacted, whereas alcohol use did not predict the GPS, although the rate was higher in the GPS.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…In addition, Oswald et al (80) suggested that early trauma may lead to enhanced sensitivity to substances and that this mechanism may underlie increased vulnerability for drug abuse. In a recent study conducted among adolescents, victimization experiences were associated with increased contemporaneous substance use, while the impact on substance use declined over time (34). Lifetime tobacco and drug use predicted the GPS in the present study, and their effects also interacted, whereas alcohol use did not predict the GPS, although the rate was higher in the GPS.…”
Section: Discussioncontrasting
confidence: 54%
“…According to a previous study, internalizing symptoms and anger may be psychological mediators of the relationship between childhood maltreatment and adolescent violent behavior (74). Alcohol, tobacco, and other drug use may be related with witnessing, perpetrating, and being a victim of violence (2,(30)(31)(32)(33)(34). One frequently cited explanation is that substance use places individuals at increased risk for violence exposure (76), perhaps through lifestyle factors such as association with violent peers and engagement in illegal activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A potent negative environmental influence, violence exposure, has been associated with early initiation of alcohol use (Taylor and Kliewer, 2006; Bossarte and Swahn, 2008), marijuana use (Mason, 2010; Richardson et al, 2013), cocaine use (Delaney-Black et al, 2011), and general substance use (Pinchevsky et al, 2014) for adolescents. Repeated exposure to violence is reported to set the stage for greater rates of substance abuse and other mental and physical health problems later in development (Moffitt, 2013).…”
Section: Introductionmentioning
confidence: 99%